Development of a Deoxyribonucleic Acid Vaccine Against Enterovirus 71 - Wong, Siew Tung (2005)
Enterovirus 71 (EV71) is a major causative viral agent responsible for large outbreaks of hand,foot and mouth disease (HFMD), a common rash illness in children and infants.There is no effective antiviral treatment for severe EV71 infections and no vaccine is available. The objectives of this study were to design and constructa DNA vaccine against Enterovirus 71 using the viral capsid protein(VP1) gene of EV71 and to verify the functionality of the DNA vaccine in vitro and in vivo.The VP1 gene of EV71 isolate S2/86/1 and isolate 410/4 obtained from Prof.Mary Jane Cardosa,Universiti Malaysia Sarawak (UNIMAS) were amplified using PCR and then inserted into a eukaryotic expression vector,pVAX1.The 3.9 kb recombinant constructs were transformed into competent E.coli cells and the positive clones were screened and selected using PCR analysis,restriction digestion analysis and DNA sequencing. The pVAX1 vector that was successfully cloned with the VP1 gene from each of the isolate (S2/86/1 and 410/4) in the correct orientation and in-frame, were designated as pVAX1/VP1-S and pVAX1/VP1-4,respectively.The DNA vaccine constructs with the VP1 gene were shown to be expressed in a cell-free in vitro expression system. The constructs were then tested for protein expression in Vero cells.The VP1 protein was successfully expressed in the mammalian cell line and was detected using RT-PCR, Indirect Immunofluorescence Assay (IFA) and western blotting.Subsequently,in the in vivo studies,female Balb/c mice were immunized with the DNA vaccine constructs.Enzyme Linked Immunosorbent Assay (ELISA) was performed to detect the presence of anti-VP1 IgG in mice.The anti-VP1 IgG levels in mice immunized with the DNA vaccine constructs increased after the first booster but declined following the second booster.The anti-VP1 IgG in the mice immunized with the DNA vaccine constructs exhibited neutralising activity against EV71.The promising results obtained in the present study have prompted further testing to improve the expression and immunogenicity of this potential EV71 DNA vaccine